Description of community perceptions of nurse professionalism - Siti Sonniya; Ani Haryani; Lukmanulhakim Lukmanulhakim; Intan Rizkianti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Attention to the professionalism of nursing personnel is increasing in society because it has a close influence on the quality of health services. So it is important to apply the values of professionalism to nurses as a foundation to ensure the quality of nursing care. Purpose: This study was to determine the description of community perceptions of nurse professionalism. Methods: This study used a descriptive quantitative approach with a cross-sectional approach. The research sample was taken using purposive sampling technique involving 106 respondents. Data collection was carried out through the use of a nurse professionalism questionnaire that had been tested for validity and reliability to 30 residents in Serang City with a Cronbach's Alpha value of 0.884. Results: Showed that most respondents rated the professionalism of nurses in the low category (56.6%). In the sub-variables, most respondents rated humanity, justice, and humility in the high category. The percentage of respondents who rated the low and high categories on the altruism sub-variable was the same (50%). Meanwhile, on the sub-variables of integrity, advocacy, compassion, inclusiveness, autonomy, courage, and caring, respondents rated the category low. Judging from the hospital, the public gave a high assessment of nurse professionalism in Regional Public Hospitals (43.7%), Official Hospitals (43.3%), and Private Hospitals (43.2%). Conclusions: Efforts are needed to increase the value of nurses' professionalism by providing additional support through training, internal career development opportunities by moving to other units, and higher further education. Abstrak: Latar Belakang: Perhatian terhadap profesionalisme tenaga keperawatan meningkat di masyarakat karena memiliki pengaruh erat terhadap kualitas pelayanan kesehatan. Maka penting untuk menerapkan nilai-nilai profesionalisme pada perawat sebagai landasan untuk menjamin kualitas asuhan keperawatan. Tujuan: Penelitian ini adalah untuk mengetahui gambaran persepsi masyarakat terhadap profesionalisme perawat. Metode: Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan pendekatan cross-sectional. Sampel penelitian diambil menggunakan teknik purposive sampling dengan melibatkan 106 responden. Pengumpulan data dilakukan melalui penggunaan kuesioner profesionalisme perawat yang telah melalui uji validitas dan reliabilitas kepada 30 warga di Kota Serang dengan nilai Cronbach's Alpha sebesar 0,884. Hasil: Penelitian menunjukkan bahwa sebagian besar responden menilai profesionalisme perawat dalam kategori rendah (56,6%). Pada sub-variabel, sebagian besar responden menilai kemanusiaan, keadilan, dan kerendahan hati dalam kategori tinggi. Persentase responden yang menilai kategori rendah dan tinggi pada sub-variabel altruisme adalah sama (50%). Sementara itu, pada sub-variabel integritas, advokasi, compassion, inklusifitas, otonomi, keberanian, dan caring, responden menilai kategori rendah. Dilihat dari rumah sakit, masyarakat memberikan penilaian tinggi terhadap profesionalisme perawat di RS Umum Daerah (43,7%), RS Kedinasan (43,3%), dan RS Swasta (43,2%). Kesimpulan: Diperlukan upaya untuk meningkatkan nilai profesionalisme perawat dengan memberi dukungan tambahan melalui pelatihan, kesempatan pengembangan karir internal dengan pindah ke unit lain, dan pendidikan lanjutan yang lebih tinggi.